Queer Iberia : Sexualities, Cultures, and Crossings from the Middle Ages to the Renaissance - Hutcheson, Gregory S.; Blackmore, Josiah, 1959- (Book collections on Project MUSE., 1999)
The essays in this volume describe and analyze the sexual diversity that proliferated during the period between the tenth and the sixteenth centuries when political hegemony in Iberia passed from Muslim to Christian hands.